The Impacting Analysis on Multiple Species Competition - Yan, Han-Bing; Tang, Xu-Qing (Rough Sets, Fuzzy Sets, Data Mining, and Granular Computing, 2013)
Based on the predicted climatic data from 2041 to 2050 and the climatic data and the distribution data of the three tree species that Larix gmelinii, Betula platyphylla Suk and Picea koraiensis Nakai from 1981 to 1990 in Northeast China, 12 climatic factor indicators are extracted by using the theory and methods of hierarchical clustering and fusion technology related fuzzy proximity relations. The prediction mathematical model of tree species distribution is built by using the statistical theory and methods, its algorithm is studied, and the predicted distribution figures produced by single tree species and the ones produced by multiple tree species competition are obtained. By analyzing the prediction, the distributions of three tree species drift to the north. Furthermore, the climate change and competition among species are the main impact factors for predicting distributions of three tree species.